Functional fibers for robotic fabrics. Issue 1 (28th August 2018) - Buckner, Trevor L; Kramer-Bottiglio, Rebecca
Abstract: Fabrics have conventionally been passive materials with static properties, leveraging the mechanical, optical, and thermal properties of networks of fibers. Recently, however, the emergence of functional fibers with dynamic properties has begun to disrupt this conventional definition. Engineers have begun to explore new materials and manufacturing processes for actuating, sensing, and variable-stiffness fibers, and the integration of these functional fibers into dynamic, robotic fabrics. This review discusses recent developments in functional fibers and speculates on their utility in future robotic fabrics.